The Effect of Digital Marketing Strategy, Brand Trust, and Customer Expectations on Online Purchasing Decisions on E-Commerce in West Java - Cindrakasih, RR Roosita; Mu'min, Halek; Jumui, Jumui; Utami , Eva Yuniarti; Agus Tapaningsih , Weni Indah Doktri (Westscience Press, 2024)
This study investigates the impact of digital marketing strategy, brand trust, and customer expectations on online purchase decisions in the e-commerce sector in West Java, Indonesia. Through quantitative analysis involving 145 respondents, data was collected using a structured questionnaire to measure the specified constructs. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was used to analyse the relationships between variables. Drawing upon theoretical frameworks and empirical evidence, hypotheses are formulated to investigate the relationships between digital marketing strategy, brand trust, customer expectations, and online purchasing decisions. The findings contribute to a deeper understanding of consumer behaviour in digital marketplaces and offer actionable insights for businesses aiming to optimise their marketing strategies and increase consumer engagement in the e-commerce sector in West Java.